INTELLIGENT SOLVING MACHINES ON MODERN PARALLEL ARCHITECTURES - Koval, Valeriy N.; Savyak, Volodymyr V. (International Journal of Computing, 2014)
The paper considers the creation of intelligent solving machines and the arrangement of parallel programming in intelligent distributed multiprocessor systems based on them. There are proposed some main concepts. A system is designed for programming in the C+Graph high-level language. The ideology proposed can be considered as an efficient development of structural high-level language interpretation when applied to multi-microprocessor systems. Equipment structure of the basic version of intelligent solving machines is considered and some characteristics are discussed.